A biographical study of P.R Mphephu (1925-1988), with special reference to political leadership in a twentieth century South African society - Khangala, Peterrocks Benjamin (University of Limpopo, 1999)
Refer to the document
Thesis (M. A.) -- University of the North, 1999
Keywords: Political leadership; Venda people; Traditional leaders; Chietancy; Political leadership -- South Africa -- Limpopo; Mphephu P.R. -- History and criticism; Venda(African people)